Cardiac-based vagus nerve stimulation reduced seizure duration in a patient with refractory epilepsy. (March 2015) - Hampel, Kevin G.; Vatter, Hartmut; Elger, Christian E.; Surges, Rainer
Highlights: The Aspire VNS-device was implanted in a patient with refractory epilepsy. The effects of heart rate-triggered VNS-pulses on seizure duration were evaluated. The novel VNS-device detected seizures with high sensitivity but low specificity. Responsive VNS-stimulation significantly reduced seizure duration. Abstract: Purpose: A novel vagus nerve stimulation (VNS) device was recently approved in Europe which rapidly detects increases in heart rates (HR) and applies an additional stimulus if HR-increases exceed a given threshold. The effects of HR-triggered VNS-pulses on seizures were not reported yet under controlled conditions. Here, we quantified the effects of HR-triggered VNS-pulses on the seizure duration in one patient. Methods: The novel VNS device was implanted in a 29-year old man with refractory epilepsy. After implantation, the patient underwent video-EEG telemetry for 68 h with no changes in anticonvulsant drugs. On the first day the patient only received sham-stimulation. During the following 46 h HR-related VNS-stimulation was set to 2 mA. Seizure duration was determined based on clinical signs. Results: Twelve stereotypical seizures were recorded (six during sham- and six during the active stimulation). The VNS device recognised a total of 139 events as a seizure and correctly identified 11 seizures. The HR-triggered VNS-stimulation significantly reduced the total seizure duration from 33.2 ± 4.8 s to 26.5 ± 5 s and the remaining seizure duration after the onset of the extra-stimulation from 27.8 ± 4.3 s to 16.2 ± 3.2 s. With the given configuration in this patient, sensitivity and specificity of HR-based seizure-detection amounted to 92% and 13.5%, respectively. Conclusions: This case illustrates that VNS-stimulation in response to seizure-related HR-increases is able to significantly reduce seizure duration. Despite the limitations of our case, its promising results should prompt larger studies to confirm the clinical benefit of this novel device.